Adsorption and desorption of CO on Pt(1 1 1): A comprehensive analysis - Mcewen, Jean-Sabin; Payne, Stephen H.; Kreuzer, Hans Jürgen; Kinne, Martin; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2003)
A comprehensive theory of the adsorption of CO on Pt(1 1 1) is developed to describe equilibrium properties as well as the adsorption and desorption kinetics. The basis is a multi-site lattice gas model which allows for adsorption at on-top and bridge sites, and includes site exclusion and lateral interactions out to second neighbour unit cells as well as a mean field to account for long ranged dipolar interactions between CO molecules. The theory reproduces the coverage and temperature dependence of pressure isotherms, partial coverages, heat of adsorption, total sticking coefficients, and isothermal and temperature-programmed desorption rates. The quality of the fits and the internal consistency of the theory are such that a number of minor inconsistencies in available experimental data can be identified and discussed. © 2003 Elsevier B.V. All rights reserve
Keywords: Equilibrium thermodynamics and statistical mechanics; Models of surface kinetics; X-ray photoelectron spectroscopy; Adsorption kinetics; Sticking; Thermal desorption; Platinum; Carbon monoxide